Rapid Return for School Refusal: A School-Based Approach Applied With Japanese Adolescents - Maeda, Naoki; Heyne, David (Frontiers in Psychology, 2019)
Cognitive behavioral therapy (CBT) is often effective in the treatment of school refusal (SR). Its usefulness is limited, however, if youth displaying SR also refuse to attend treatment sessions. In these cases parents and school staff may consider using school-based interventions that do not rely on face-to-face assessment and treatment with the young person. The current study examined the effectiveness of a school-based intervention applied in Japan to achieve rapid return to school among adolescents displaying SR. Between 2009 and 2015, the parents of 62 adolescents displaying SR were invited to implement a school-based rapid return approach. Thirty-nine parents agreed to implement the approach and 23 decided to wait until their child spontaneously attended school. Of the 39 cases in which the approach was implemented, 28 adolescents (72%) resumed attendance at their original school, 2 (5%) transferred to another school, and 9 (23%) did not resume attendance. In contrast, all 23 non-intervention cases continued to refuse to attend school for three months or longer, and none of these adolescents returned to regular school attendance within nine months. This study tentatively suggests that the rapid return approach may be an effective form of intervention for adolescents displaying SR and simultaneously refusing to attend individual therapy. Because this approach is ethically complex, involving forced school attendance in adolescence, it should only be employed under specific circumstances. These circumstances are discussed.